High-strength titanium alloy material and preparation method and application thereof
By introducing modified carbon fibers and high-entropy MAX ceramics into a titanium alloy matrix to form a nanolayered structure, the problem of insufficient strength and high-temperature resistance of titanium alloy materials in the field of high-performance equipment is solved, and the high strength and high-temperature stability of the material are improved.
Patent Information
- Application Number
- CN202511839643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-08
- Publication Date
- 2026-01-13
AI Technical Summary
Existing titanium alloy materials are insufficient in terms of strength, high temperature resistance, or corrosion resistance when used in high-performance equipment, and the introduction of reinforcing phases presents problems such as interfacial reactions and complex preparation processes.
A combination of 84-93 wt% titanium alloy matrix, 5-10 wt% modified carbon fiber and 2-6 wt% high-entropy MAX ceramic is used to form a nano-layered structure through the preparation and sintering process of modified carbon fiber and high-entropy MAX ceramic, thereby enhancing the strength and toughness of titanium alloy.
It significantly improves the mechanical strength and high-temperature performance of titanium alloy materials, enhances interfacial bonding, increases material density and fatigue resistance, strengthens the excellent compatibility between the enhanced phase and the titanium matrix, and significantly improves the overall performance of the material through a strengthening mechanism.
Smart Images

Figure CN121320844A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of titanium alloy, and particularly relates to a high-strength titanium alloy material and a preparation method and application thereof. BACKGROUND
[0002] Titanium alloy is an important structural material developed in the middle and late 20th century, has low density, high specific strength, high corrosion resistance and good biocompatibility, and has excellent comprehensive performance, and is widely applied in the technical fields of aerospace, ship transportation, weapons, petroleum chemical industry, medical treatment and the like, for example, TC4 titanium alloy is applied to a stepped shaft of an oil pickup pipe of petroleum equipment, TA2G titanium alloy is applied to a stirring shaft of petroleum equipment, and TC4ELI titanium alloy is applied to a cabin body, a cylinder body, a pipeline and the like of ship and marine engineering equipment, which can effectively improve equipment safety and reliability, reduce equipment quality, reduce equipment damage and maintenance frequency, prolong equipment service life and save production cost. With the gradual expansion of the application range of titanium alloy, the service conditions of some high-performance equipment fields are increasingly severe, higher requirements are put forward for the strength and high-temperature resistance or corrosion resistance of the titanium alloy, and the design and development of the titanium alloy material also need continuous updating and progress.
[0003] The common strengthening methods of titanium alloy mainly include alloy element strengthening, heat treatment strengthening, interface strengthening and composite strengthening, and the introduction of reinforcing phases in the alloy matrix through compounding is a relatively popular research idea at present. The reinforcing phases of the titanium alloy material mainly have three forms of continuous fibers, whiskers and particles, the composition of the reinforcing phases can be selected from cermet, oxide and intermetallic compound, and the generation method of the reinforcing phases can be divided into traditional external method and in-situ reaction self-generation method, which can significantly improve the comprehensive performance of the titanium alloy such as strength, hardness and modulus. However, the introduction of reinforcing phases also has problems such as interface reaction, anisotropic defects and complex preparation process, and therefore the reinforcing phases need to be modified or innovated to improve the overall performance of the titanium alloy material. SUMMARY
[0004] The first purpose of the application is to provide a high-strength titanium alloy material, which has high mechanical strength and excellent overall performance.
[0005] The second purpose of the application is to provide a preparation method of the high-strength titanium alloy material.
[0006] The third purpose of the application is to provide an application of the high-strength titanium alloy material in a stepped shaft.
[0007] In order to achieve the above purposes, the technical scheme adopted by the application is as follows: A high-strength titanium alloy material, the high-strength titanium alloy material is composed of 84-93 wt% titanium alloy matrix, 5-10 wt% modified carbon fiber and 2-6 wt% high-entropy MAX ceramic. The modified carbon fiber is prepared by the following preparation process: (1) adding metatitanic acid and activated carbon powder into water, stirring to paste under heating condition to obtain a precursor sol; (2) coating the precursor sol on the surface of carbon fiber, drying, and calcining under nitrogen environment to obtain the modified carbon fiber.
[0008] Further, in step (1), the ratio of the use amount of metatitanic acid, activated carbon powder and water is 1 g: (3-5) g: (20-25) mL; the temperature of heating is 50-75 ℃.
[0009] Further, in step (2), the mass ratio of the precursor sol and carbon fiber is 100: (40-100).
[0010] Further, in step (2), the temperature of drying is 120-140 ℃, and the time is 8-12 h; the temperature of calcining is 1500-1700 ℃, and the time is 1-3 h.
[0011] Further, the high-entropy MAX ceramic is prepared by the following preparation process: Ti, V, Y, Nb, Zr, Al and C are ball-milled and mixed in ethanol, and a high-entropy MAX ceramic is obtained after sintering treatment.
[0012] Further, the molar ratio of Ti, V, Y, Nb, Zr, Al and C is (1-1.2): (1-1.2): (1-1.2): (1-1.2): (1-1.2): (2.5-3.0): (5-6); the temperature of sintering treatment is 1100-1300 ℃, and the time is 20-50 min.
[0013] Further, the titanium alloy matrix is composed of raw materials in the following weight percentages: Al 5.8-6.5 wt%, V 3.7-4.3 wt%, Mo 3.2-4.2 wt%, Sc 0.2-0.7 wt%, Fe≤0.3 wt%, C≤0.1 wt%, and the balance is Ti.
[0014] The preparation method of the high-strength titanium alloy material described above comprises the following steps: The titanium alloy substrate, modified carbon fiber and high-entropy MAX ceramic are ball-milled and mixed, pre-pressed and molded, and then sintered under nitrogen environment to obtain a titanium alloy material.
[0015] Further, the pressure of pre-pressing molding is 10-20 MPa; the temperature of sintering is 1000-1200 ℃, and the time is 1-3 h.
[0016] The application of the aforementioned high-strength titanium alloy materials in stepped shafts.
[0017] The beneficial technical effects of this invention are as follows: 1. This invention adds high-entropy MAX ceramic material as a reinforcing phase to a titanium alloy matrix. MAX material combines the excellent properties of both metallic and ceramic materials, such as low density, high modulus, and resistance to high-temperature oxidation. After multi-principal element high-entropy, the nanolayered structure is further optimized, and both strength and hardness are significantly improved. As a reinforcing phase for titanium alloy materials, it can induce a particle load-bearing strengthening effect. Furthermore, the nanoscale size of MAX material forms a pinning effect with the grain boundaries of the titanium matrix, hindering dislocation movement and causing grain refinement strengthening and Orovan strengthening. These strengthening mechanisms can significantly improve the mechanical strength of titanium alloy materials.
[0018] 2. This invention adds modified carbon fiber as a reinforcing phase to a titanium alloy matrix. Carbon fiber has low density, high modulus, and high strength, and as a reinforcing phase for titanium alloys, it can significantly improve the strength and fatigue resistance of the material. However, there is an interfacial bonding problem between carbon fiber and the titanium alloy matrix. During sintering, it reacts with the matrix to form a brittle TiC phase, which affects the strength and toughness of the material. The carbon fiber is modified by coating its surface with titanium carbonitride. Titanium carbonitride has good physical and chemical compatibility with the titanium matrix, and their coefficients of thermal expansion are similar. Moreover, titanium carbonitride has excellent high-temperature stability. After modification, the bonding between the fiber and the alloy matrix is good, and the density is high after sintering. The strength and high-temperature performance of the material are significantly improved. Attached Figure Description
[0019] Figure 1 This is a scanning electron microscope image of the modified carbon fiber obtained in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the high-entropy MAX ceramic prepared in Example 1 of the present invention. Detailed Implementation
[0020] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention. Specific conditions not specified in the embodiments are performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used are conventional products obtained through commercial channels.
[0021] (I) Implementation Examples Example 1 Example 1 provides a high-strength titanium alloy material, which is composed of 88 wt% titanium alloy matrix, 8 wt% modified carbon fiber and 4 wt% high-entropy MAX ceramic; the titanium alloy matrix is composed of the following raw materials by weight percentage: Al 6.1 wt%, V 4.1 wt%, Mo 3.7 wt%, Sc 0.5 wt%, Fe≤0.3 wt%, C≤0.1 wt%, and the balance is Ti.
[0022] The modified carbon fiber is prepared by the following process: (1) According to the ratio of metatitanic acid, activated carbon powder and water, 1 g: 4 g: 23 mL, the water is divided into 4 parts in advance. The metatitanic acid and activated carbon powder are mixed and added to one part of the water. The mixture is stirred at 60 °C until the solution becomes a paste. The water is added and stirred repeatedly until it becomes a paste. After all the water is added, a paste-like precursor sol is obtained. (2) The precursor sol was coated onto the surface of the carbon fiber at a mass ratio of 5:3 to 5:3. After drying at 120°C for 10 h, the carbon fiber was transferred to a tube furnace, nitrogen gas was introduced at a flow rate of 0.6 L / min, and then calcined at 1600°C for 2 h to obtain the modified carbon fiber. The scanning electron microscope image of the modified carbon fiber prepared in this embodiment is shown below. Figure 1 As shown.
[0023] The high-entropy MAX ceramic is prepared by the following process: According to the molar ratio of Ti, V, Y, Nb, Zr, Al, and C of 1:1:1:1:1:2.8:5, Ti, V, Y, Nb, Zr, Al, and C were ball-milled in anhydrous ethanol for 4 h, and then sintered at 1200 °C for 30 min to obtain high-entropy MAX ceramics. The scanning electron microscope image of the high-entropy MAX ceramics prepared in this example is shown below. Figure 2 As shown.
[0024] This embodiment also provides a method for preparing the above-mentioned high-strength titanium alloy material, the specific steps of which are as follows: The raw materials were weighed according to the above mass ratio. The titanium alloy matrix, modified carbon fiber and high-entropy MAX ceramic ball mill were mixed and loaded into the mold. The mixture was pre-pressed with a pressure of 15 MPa and then transferred to a sintering furnace. The mixture was sintered at 1200 °C for 2 h in a nitrogen atmosphere and cooled to room temperature to obtain a high-strength titanium alloy material.
[0025] Example 2 Example 2 provides a high-strength titanium alloy material, which is composed of 84 wt% titanium alloy matrix, 10 wt% modified carbon fiber and 6 wt% high-entropy MAX ceramic; the titanium alloy matrix is composed of the following raw materials by weight percentage: Al 5.8 wt%, V 3.7 wt%, Mo 3.2 wt%, Sc 0.2 wt%, Fe≤0.3 wt%, C≤0.1 wt%, and the balance is Ti.
[0026] The modified carbon fiber is prepared by the following process: (1) According to the ratio of metatitanic acid, activated carbon powder and water, 1 g: 3 g: 20 mL, the water is divided into 4 parts in advance. The metatitanic acid and activated carbon powder are mixed and added to one part of the water. Stir at 50 °C until the solution becomes a paste. Repeat the addition of water and stirring until it becomes a paste. After all the water is added, a paste-like precursor sol is obtained. (2) The precursor sol was coated on the surface of the carbon fiber according to the mass ratio of precursor sol to carbon fiber of 5:2. After drying at 120℃ for 8 h, it was transferred to a tube furnace and nitrogen gas was introduced at a flow rate of 0.4 L / min. Then it was calcined at 1500℃ for 1 h to obtain modified carbon fiber.
[0027] The high-entropy MAX ceramic is prepared by the following process: According to the molar ratio of Ti, V, Y, Nb, Zr, Al and C of 1:1:1:1:1:2.5:5, Ti, V, Y, Nb, Zr, Al and C were added to anhydrous ethanol and ball-milled for 2 h, and then sintered at 1100 ℃ for 20 min to obtain high-entropy MAX ceramics.
[0028] This embodiment also provides a method for preparing the above-mentioned high-strength titanium alloy material, the specific steps of which are as follows: The raw materials were weighed according to the above mass ratio. The titanium alloy matrix, modified carbon fiber and high-entropy MAX ceramic ball mill were mixed and loaded into the mold. The mixture was pre-pressed with 10 MPa pressure and then transferred to a sintering furnace. The mixture was sintered for 1 h in a nitrogen atmosphere at 1000 °C and cooled to room temperature to obtain a high-strength titanium alloy material.
[0029] Example 3 Example 3 provides a high-strength titanium alloy material, which is composed of 93 wt% titanium alloy matrix, 5 wt% modified carbon fiber and 2 wt% high-entropy MAX ceramic; the titanium alloy matrix is composed of the following raw materials by weight percentage: Al 6.5 wt%, V 4.3 wt%, Mo 4.2 wt%, Sc 0.7 wt%, Fe≤0.3 wt%, C≤0.1 wt%, and the balance is Ti.
[0030] The modified carbon fiber is prepared by the following process: (1) According to the ratio of metatitanic acid, activated carbon powder and water, 1 g: 5 g: 25 mL, the water is divided into 4 parts in advance. The metatitanic acid and activated carbon powder are mixed and added to one part of the water. Stir at 75 °C until the solution becomes a paste. Repeat the addition of water and stirring until it becomes a paste. After all the water is added, a paste-like precursor sol is obtained. (2) The precursor sol was coated on the surface of the carbon fiber at a mass ratio of 1:1 to the precursor sol. After drying at 140°C for 12 h, it was transferred to a tube furnace and nitrogen gas was introduced at a flow rate of 0.9 L / min. The carbon fiber was then calcined at 1700°C for 3 h to obtain the modified carbon fiber.
[0031] The high-entropy MAX ceramic is prepared by the following process: According to the molar ratio of Ti, V, Y, Nb, Zr, Al and C of 1.2:1.2:1.2:1.2:1.2:3:6, Ti, V, Y, Nb, Zr, Al and C were added to anhydrous ethanol and ball-milled for 6 h, and then sintered at 1300 ℃ for 50 min to obtain high-entropy MAX ceramics.
[0032] This embodiment also provides a method for preparing the above-mentioned high-strength titanium alloy material, the specific steps of which are as follows: The raw materials were weighed according to the above mass ratio. The titanium alloy matrix, modified carbon fiber and high-entropy MAX ceramic ball mill were mixed and loaded into the mold. The mixture was pre-pressed under a pressure of 20 MPa and then transferred to a sintering furnace. The mixture was sintered at 1200 °C for 3 h under a nitrogen atmosphere and cooled to room temperature to obtain a high-strength titanium alloy material.
[0033] (ii) Comparative Example Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the high-entropy MAX ceramic in Example 1 is replaced with titanium aluminum carbide Ti2AlC.
[0034] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that the modified carbon fiber in Example 1 is replaced with carbon fiber.
[0035] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the modified carbon fiber in Example 1 is replaced with a mixture of carbon fiber and titanium carbonitride, with a mass ratio of carbon fiber to titanium carbonitride of 10:1.
[0036] (III) Test Examples The titanium alloy materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests.
[0037] Mechanical testing: The mechanical properties of the titanium alloy materials in Examples 1-3 and Comparative Examples 1-3 were tested in accordance with GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature". The results are shown in Table 1.
[0038] Table 1. Test results of mechanical properties of titanium alloy materials As shown in Table 1, the high-strength titanium alloy materials prepared in Examples 1-3 of this invention exhibit high mechanical strength and excellent overall performance. Compared to Example 1, Comparative Example 1 replaced the high-entropy MAX ceramic in Example 1 with titanium aluminum carbide, Comparative Example 2 replaced the modified carbon fiber in Example 1 with carbon fiber, and Comparative Example 3 replaced the modified carbon fiber in Example 1 with a mixture of carbon fiber and titanium carbonitride. The mechanical properties of Comparative Examples 1-3 all decreased to varying degrees. Specific analysis reveals that: on the one hand, this invention adds high-entropy MAX ceramic material as a reinforcing phase to the titanium alloy matrix. MAX material possesses the excellent properties of both metallic and ceramic materials, such as low density, high modulus, and high-temperature oxidation resistance. After multi-principal element high-entropy, the nanolayered structure is further optimized, significantly improving both strength and hardness. As a reinforcing phase for titanium alloy materials, it can induce a particle-bearing strengthening effect. Furthermore, the nanoscale size of MAX material forms a pinning effect with the grain boundaries of the titanium matrix, hindering dislocation movement and causing grain refinement and Orovan strengthening. These strengthening mechanisms can significantly improve the mechanical strength of the titanium alloy material. On the other hand, this invention… Ming added modified carbon fiber as a reinforcing phase to a titanium alloy matrix. Carbon fiber has low density, high modulus, and high strength, and as a reinforcing phase, it can significantly improve the strength and fatigue resistance of the titanium alloy. However, there is an interfacial bonding problem between carbon fiber and the titanium alloy matrix. During sintering, it reacts with the matrix to form a brittle TiC phase, which affects the strength and toughness of the material. Modification was achieved by coating the surface with titanium carbonitride. Titanium carbonitride has good physical and chemical compatibility with the titanium matrix, and their coefficients of thermal expansion are similar. In addition, titanium carbonitride has excellent high-temperature stability. After modification, the bonding between the fiber and the alloy matrix is good, and the density is high after sintering. The strength and high-temperature performance of the material are significantly improved.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. Based on the present invention, some modifications or substitutions can be made, but these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of protection claimed by the present invention.
Claims
1. A high-strength titanium alloy material, characterized in that, The high-strength titanium alloy material is composed of 84-93 wt% titanium alloy matrix, 5-10 wt% modified carbon fiber and 2-6 wt% high-entropy MAX ceramic; The modified carbon fiber is prepared by the following process: (1) Add metatitanic acid and activated carbon powder to water and stir under heating conditions until a paste is formed to obtain a precursor sol; (2) The precursor sol is coated on the surface of carbon fiber, dried and then calcined in a nitrogen atmosphere to obtain modified carbon fiber.
2. The high-strength titanium alloy material according to claim 1, characterized in that, In step (1), the ratio of metatitanic acid, activated carbon powder and water is 1 g: (3-5) g: (20-25) mL; the heating temperature is 50-75 ℃.
3. The high-strength titanium alloy material according to claim 1, characterized in that, The mass ratio of the precursor sol to carbon fiber in step (2) is 100:(40-100).
4. The high-strength titanium alloy material according to claim 1, characterized in that, The drying temperature in step (2) is 120-140 ℃ and the time is 8-12 h; the calcination temperature is 1500-1700 ℃ and the time is 1-3 h.
5. The high-strength titanium alloy material according to claim 1, characterized in that, The high-entropy MAX ceramic is prepared by the following process: Ti, V, Y, Nb, Zr, Al and C were added to ethanol, ball-milled and mixed, and then sintered to obtain high-entropy MAX ceramics.
6. The high-strength titanium alloy material according to claim 5, characterized in that, The molar ratio of Ti, V, Y, Nb, Zr, Al and C is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(2.5-3.0):(5-6); the sintering temperature is 1100-1300 ℃ and the time is 20-50 min.
7. The high-strength titanium alloy material according to claim 1, characterized in that, The titanium alloy matrix is composed of the following raw materials in weight percentage: Al 5.8-6.5 wt%, V 3.7-4.3 wt%, Mo 3.2-4.2 wt%, Sc 0.2-0.7 wt%, Fe≤0.3 wt%, C≤0.1 wt%, with the balance being Ti.
8. A method for preparing a high-strength titanium alloy material according to any one of claims 1-7, characterized in that, Includes the following steps: The titanium alloy substrate, modified carbon fiber, and high-entropy MAX ceramic ball mill were mixed, pre-pressed, sintered in a nitrogen atmosphere, and cooled to obtain the titanium alloy material.
9. The method for preparing high-strength titanium alloy material according to claim 8, characterized in that, The pre-pressing pressure is 10-20 MPa; the sintering temperature is 1000-1200 ℃, and the time is 1-3 h.
10. The application of the high-strength titanium alloy material according to any one of claims 1-6 in stepped shafts.